2015
DOI: 10.1080/15476286.2015.1100795
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-mediated microRNA transfer plays a role in radiation-induced bystander effect

Abstract: Bystander effects can be induced through cellular communication between irradiated cells and non-irradiated cells. The signals that mediate this cellular communication, such as cytokines, reactive oxygen species, nitric oxide and even microRNAs, can be transferred between cells via gap junctions or extracellular medium. We have previously reported that miR-21, a well described DDR (DNA damage response) microRNA, is involved in radiation-induced bystander effects through a medium-mediated way. However, the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
121
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 44 publications
2
121
0
Order By: Relevance
“…Irradiation of a given cell can trigger the upregulation of specific miRNAs such as those involved in DNA damage response functions [32]. Through packaging of these miRNAs within vesicles such as exosomes, the miRNAs are easily exchanged intercelluarly and can subsequently elicit bystander effects in recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation of a given cell can trigger the upregulation of specific miRNAs such as those involved in DNA damage response functions [32]. Through packaging of these miRNAs within vesicles such as exosomes, the miRNAs are easily exchanged intercelluarly and can subsequently elicit bystander effects in recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have raised that the extracellular miRNAs may play an important role in regulating intercellular communication and thus have implications in tumor biology [13, 16, 29, 30, 36]. In addition, some evidences indicate that extracellular miRNAs are relevant to RIBE [24, 25]. However, there is no literature concerning the role of radiation-induced extracellular miRNAs in regulating cell radiosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed that many kinds of diffusible signaling factors contribute to the generation of RIBE, including reactive oxygen species (ROS), reactive nitrogen species (RNS), cytochrome-c and cytokines [2123]. Recently, it was reported that miR-663 and miR-21 were involved in the RIBE through a medium-mediated pathway [24, 25]. However, the characteristics of extracellular miRNA expressions responding to IR and the potential roles of miRNAs in regulating cell radiosensitivity are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, transfection of miR-21 mimics into MRC-5 cells induced similar effects, suggesting a role for miR-21 in mediating RIBE. In a follow-up study, the same group demonstrated that exosomes isolated from irradiated CM could induce bystander effects by mediating miR-21 transfer from irradiated to bystander cells (149). Inhibition of miR-21 before irradiation blunted these effects, suggesting that exosome-mediated miR-21 transfer plays an important role in RIBE.…”
Section: Exosomesmentioning
confidence: 99%